The relation of the “four properties” and fluid identification of the carboniferous weathering crust volcanic reservoir in the Shixi Oilfield, Junggar Basin, China - Fu, Lei; Qin, Zhangjin; Xie, An; Chen, Liang; Li, Junfei; Wang, Nan; Qin, Qirong; Mao, Kailan (Frontiers in Earth Science, 2022)
This study addresses the poor physical properties of the Shixi Oilfield reservoir, which consists of a weathered Carboniferous volcanic crust with strong heterogeneity and in which logging identification and evaluation are difficult. Using the lithology, lithofacies, and reservoir space characteristics of volcanic materials, this comprehensive study uses core, well logging, mud logging, and production testing data to analyze the relationship among the lithology, physical properties, electrical properties, and oil-bearing properties (referred to as the “four properties”) of weathered Carboniferous volcanic crust in addition to fluid identification. (1) The lithology of Carboniferous volcanic crust is dominated by breccia lava, agglomerate, banded lava, and compact tuff, and the lithofacies are mainly effusive facies. Secondary pores and tectonic fissures are important reservoir spaces, and the corrosion-fracture pores are significant for reservoir properties. (2) The “four properties” of volcanic reservoirs in the study area have clear relationships. On this basis, data on the electrical properties of the material, such as interval transit time, density, and neutron, were used to establish a logging interpretation model of the properties and oil saturation of the volcanic rock. (3) Using the resistivity-porosity cross-plot method, normal probability distribution method, and Rt/Rxo-Rt cross-plot method, volcanic reservoir fluids were identified with coincidence rates of 80%, 63.63%, and 63.63%, respectively. The cross-plot method determines lower limits of the reservoir’s physical properties and oil saturation, yielding porosity>9%, permeability>0.2 mD, and oil saturation>45%.